1973
DOI: 10.1111/j.1469-8986.1973.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Immediate Feedback Upon Voluntary Control of Salivary Rate

Abstract: Thirteen human subjects (Ss) were given immediate auditory feedback concerning their salivary rates and were asked both to increase and to decrease their rates during a series of 30‐sec trials. Significant decreases, but not increases, in salivary rate were obtained relative to baseline. During the second half of the experiment, when feedback was omitted until the end of each trial, Ss maintained significant differential response rates between increase and decrease trials, but the reliability of decreases from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…This study confirms earlier findings (Brown and Katz, 1967;Delse and Feather, 1968;Frezza and Holland, 1971;Wells et al, 1973) that salivation can be influenced. Such findings, as Schwartz (1978) asserts, make it difficult to distinguish voluntary from involuntary responses and suggest that a rather broad range of responses can be manipulated by the use of operant procedures.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This study confirms earlier findings (Brown and Katz, 1967;Delse and Feather, 1968;Frezza and Holland, 1971;Wells et al, 1973) that salivation can be influenced. Such findings, as Schwartz (1978) asserts, make it difficult to distinguish voluntary from involuntary responses and suggest that a rather broad range of responses can be manipulated by the use of operant procedures.…”
Section: Discussionsupporting
confidence: 95%
“…Some data, however, are available that suggest that operant procedures and feedback can influence salivation in humans, and lower animals (Brown and Katz, 1967;Delse and Feather, 1968;Frezza and Holland, 1971;Miller and Carmona, 1967;Wells et al, 1973). Furthermore, and even more pertinent to the uses of the salivary response measure cited above, Barber et al (1964) reported that subjects were able to alter salivation in line with the experimenters' directions to imagine that water placed on the tongue was a previously tasted solution of citric acid and that citric acid placed on the tongue was water.…”
Section: Introductionmentioning
confidence: 85%
“…This vasoconstriction in response to stimulation was similar to that reported by Sokolov [1963] in his descrip tion of the orienting reflex. Surwit et al [1976] also noted that the apparent differential ability to increase as opposed to decrease arousal-like behavior is consistent with results of studies on a voluntary control of blood pressure and heart rate [Blanchard and Young, 1973], salivation [Wells, 1973] and occipital alpha control [Paskowitz and Orne, 1974], It was thus hypothe sized that increases in sympathetic activity producing responses, such as vasoconstriction, are easier to learn with biofeedback paradigm than decreases in sympathetic activity. Lynch et al [1976] also reported difficulty in obtaining control of peripheral skin temperature in adults.…”
Section: Voluntary Control Of Peripheral Vasomotor Responsessupporting
confidence: 49%
“…These researchers used a iigorous procedure for establishing baseline (stabilization period) and for the statistical analysis of finger temperature changes by ipsitizing each subject's performance with respect to temperature change on baseline, similar to the procedure developed by Herzfeld andTaub (1977, 1980). Examples of this effect can be found in the literature on heart rate (Blanchard & Young, 1973), occipital alpha (Paskewitz & Orne, 1973), and salivation (Wells, Feather, & Headrick, 1973). Decreases were greatest if the subjects were given response-specific instructions and that temperature control was attenuated if verbal suggestions relating to decreases in skin temperature were given during training.…”
mentioning
confidence: 97%